Handbook on Concrete Block Paving - Mampearachchi, Wasantha (Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a comprehensive overview of concrete block paving (CBP). Starting with the basics, such as the history, applications, advantages and limitations of CBP, it then discusses in detail the structural behavior, construction process, and design support conditions, covering topics like specifications for blocks and laying patterns, field performance and mix design for ICBP. Lastly, it examines good CBP practices and maintenance.